Meningkatkan Minat Kuliah pada Siswa Melalui Sosialisasi dan Motivasi di SMA Negeri 1 Woyla Barat - Ligar Abdillah; Yeni Sri Lestari; Irma Juraida; Devi Intan Chadijah; Lilis Sariyanti; Triyanto Triyanto; Cut Irna Liyana; Fadli Afriandi; Muntaha Mardhatillah (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2023)
Increasing interest in lectures through outreach activities and providing motivation to students is an important thing to do. This activity is an important part of one of the obligations of lecturers who must carry out community service. The implementation of this activity is very much in line with the national development agenda in improving the quality of human resources through the education sector. The method of implementing this activity begins with observation and surveys to determine the condition of the school and the potential of students at SMAN 1 Woyla Barat, West Aceh District. The team conducted a pre test and post test to measure the accuracy and usefulness of the activity. The presenters explained material about tertiary institutions, selection pathways, scholarship information, inspirational stories, and motivation to increase students' insight and interest in continuing their education to tertiary institutions. The success of this activity was marked by the enthusiasm and positive response of the students who gave very good scores in the evaluation questionnaire. Activities like this need to be carried out in several underdeveloped areas so that students in those areas receive information about tertiary institutions and are motivated to continue their education at tertiary institutions.